THE INFLUENCE OF JOB CONFLICT AND JOB STRESS ON TEACHER PERFORMANCE (STUDY ON MUTIARA BUNDA KINDERGARTEN TEACHERS KARANGANYAR REGENCY) - Suyatno, Agus; Chotidjah Suhatmi, Erna; Muhtarom, Moh.; Adil Sulistyo, Hestuningtyas (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2023)
This study aims to determine the effect of job conflict and job stress on the performance of Mutiara Bunda Kindergarten teachers, the independent variable in this study is job conflict and job stress and the dependent variable is teacher performance. This research method used is using quantitative methods with an associative research level of explanation, namely to determine the effect between variables, the data source is primary data and secondary data in the form of questionnaires. The statistical methods used are the normality test, linearity test, multicollinearity test, heteroscedasticity test, autocorrelation analysis, multiple regression analysis, partial correlation analysis, and determination analysis. Based on the calculation of the hypothesis test, the F-count value is 54.858 while the F-table is 3.49 (54.858> 3.49), meaning that Hâ‚€ is rejected and Ha is accepted, meaning that there is a positive and significant influence between work conflict and work stress on the performance of Mutiara Bunda Kindergarten teachers in Karanganyar Regency.